PERAN BIOMASA MANGROVE DALAM MENYIMPAN KARBON DI KUBU RAYA, KALIMANTAN BARAT - N M Heriyanto; Endro Subiandono (Jurnal Analisis Kebijakan Kehutanan, 2016)
One of the problems in Kubu Raya mangrove forest area is forest loss every year, this is due to conversion of mangrove forest land to settlements and illegal logging. The goal of this study is to obtain information about the role of mangrove forests and forest management policies. Plots were made at three places, each had ten sample of 10x10 m size for the inventory of trees with distance between plots of 50 m; sub plot in the plot were made, with the size  of 5x5 m for the inventory to sapling and 2x2 m  for the inventory of seedling.  The results showed that in the mangrove forests found 20 species with four dominant species Rhizophora apiculata, Bruguiera gymnorhyza, Sonneratia alba and Xylocarpus moluccensis that have great potential in mitigating global warming because mangroves are able to absorb large amount of CO,2 that is Rhizophora apiculata, Bruguiera gymnorhyza, Sonneratia alba and 2, that is Xylocarpus moluccensis. Total biomass of study sites was 438.79 tons/ha (equivalent to 219.53 tons C/ha or 805.68 tons CO/ha). Mangrove conservation needs to be done  holistically and cooperation  among the parties, including the Ministry of   2 Environment and Forestry, Ministry of Maritime and Fisheries Affairs and Local Government, in order to avoid overlapping policies.